1997
DOI: 10.1017/s0003598x00085744
|View full text |Cite
|
Sign up to set email alerts
|

‘Strange paintings’ and ‘mystery races’: Kimberley rockart, diffusionism and colonialist constructions of Australia's Aboriginal past

Abstract: Amongst the most striking and the most handsome of ancient Australian relics are the Bradshaw paintings of the Kimberley, in the remote northwest of the continent, uncertainly dated but seemingly most ancient. According to one published view, the Bradshaws are not so much ‘early Aboriginal’ as ‘pre-Aboriginal’. Issue is taken with that notion, in light of European attitudes to Aboriginal accomplishment over the last two centuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Morphological studies of the finds showed that the remains were not related to the current indigenous population. Supporting the theory that multiple migrations occurred into the Australian continent, this research rendered the current Aborigines just a phase in a long history of migrations (Dolon 1994, p. 75;McNiven and Russel 2005, p. 241;McNiven and Russell 1997). In the aftermath of new repatriation legislation in diverse states, it was requested that the Lake Mungo Remains be reburied.…”
Section: Lake Mungo Burials and A Shared Stewardship Over Cultural Simentioning
confidence: 62%
“…Morphological studies of the finds showed that the remains were not related to the current indigenous population. Supporting the theory that multiple migrations occurred into the Australian continent, this research rendered the current Aborigines just a phase in a long history of migrations (Dolon 1994, p. 75;McNiven and Russel 2005, p. 241;McNiven and Russell 1997). In the aftermath of new repatriation legislation in diverse states, it was requested that the Lake Mungo Remains be reburied.…”
Section: Lake Mungo Burials and A Shared Stewardship Over Cultural Simentioning
confidence: 62%
“…He notes: ‘why [do] prehistoric artists frequently seem to wilfully deface earlier masterpieces by superimposing them with their arguably less technologically advanced images?’ (Walsh 2000, 214, my emphasis). Implicit in this statement is the fact that new depictions constitute a ‘degenerated’ form of art in comparison to previous depictions (Redmond 2002, 56), therefore considered as a form of vandalism that destroyed previous and authentic Kimberley art (McNiven & Russell 1997, 807).…”
Section: The Role Of Superimpositions In Rock-art Researchmentioning
confidence: 99%
“…As has been argued, labelling this practice as superimposition or vandalism has different connotations on the way we interpret rock art. Walsh's work on the Kimberley has been described as portraying a Eurocentric and colonial understanding of the art (McNiven & Russell 1997, 807; 2005) that brought negative attention from social media and the general public about the origins and motivations behind Kimberley art practices. By contrast, it is proposed here that superimpositions were (and still are) a mechanism that allowed past and present inhabitants to (re)create and (re)appropriate the inherited landscape.…”
Section: The Role Of Superimpositions In Rock-art Researchmentioning
confidence: 99%
“…However, his failure to recognise the incredibly diverse nature of rock-art styles across Australia, explore other possibilities regarding cultural significance and/or stylistic links from within Australia, and consult with other Indigenous groups in the area resulted in a skewed interpretation of Gwion Gwion rock-art. Furthermore, Walsh's critics (Lewis 1997;McNiven and Russell 1997;Redmond 2002) have pointed out that the treatment of Gwion Gwion rock-art can be understood as part of a long tradition of disempowerment and alienation within a colonial and racist discourse. In a modern context, these ideas made an appearance in the argument by Walsh (1992) that no claim of Aboriginal descent could establish curatorial rights over cultural heritage that is supposed to belong to all humanity (Mowaljarlai et al 1988).…”
Section: Rock-art Research As Cultural Critiquementioning
confidence: 99%